PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS DAN SELF ESTEEM SISWA KELAS V MELALUI STRATEGI MULTIPLE INTELLIGENCES - Fauzan, -; Herman, Tatang (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2016)
Abstract: This study focused on looking at the extent to which differences in mathematical reasoning capacity building and self-esteem of students who take the multiple intelligences learning strategy and regular learning. The research subject is a fifth grade students from two different classes at the same school. There are two main instruments used to collect data that achievement test and attitude scale. Both classes are given the same instrument. The results showed that there are significant differences between the mathematical reasoning abilities of students who take the multiple intelligences learning strategy and regular learning. In contrast, there are no significant differences between self-esteem of students who take the multiple intelligences learning strategy and regular learning. The study's findings provide awareness that the teacher has a very important role in facilitating student learning. Although directed to student centered learning, but nonetheless pedagogical, especially, must be owned by a teacher. Each person may be a teacher, but not everyone can be an educator. However, students will not reach the level of proficiency is high if not under the guidance of teachers who excel.Keywords: mathematical reasoning, self-esteem, multiple intelligencesAbstrak: Penelitian ini fokus pada melihat sejauh mana perbedaan peningkatan kemampuan penalaran matematis dan self esteem siswa yang mengikuti pembelajaran dengan strategi multiple intelligences dan pembelajaran biasa. Subjek penelitian merupakan siswa kelas V yang berasal dari dua kelas yang berbeda pada satu sekolah yang sama. Terdapat dua instrumen utama yang digunakan untuk mengumpulkan data yakni tes hasil belajar dan skala sikap. Kedua kelas diberikan instrumen yang sama. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara kemampuan penalaran matematis siswa yang mengikuti pembelajaran dengan strategi multiple intelligences dan pembelajaran biasa. Sebaliknya, tidak terdapat perbedaan yang signifikan antara self esteem siswa yang mengikuti pembelajaran dengan strategi multiple intelligences dan pembelajaran biasa. Temuan penelitian memberikan kesadaran bahwa guru memiliki peranan sangat penting dalam memfasilitasi siswa belajar. Meskipun pembelajaran diarahkan kepada student centered, tetapi tetap saja kompetensi pedagogik, terutama, mesti dimiliki guru. Setiap orang mungkin bisa menjadi guru, tapi tidak setiap orang bisa menjadi pendidik. Bagaimanapun, siswa tidak akan mencapai tingkat kemampuan yang tinggi jika tidak di bawah bimbingan guru yang unggul.Kata Kunci: penalaran matematis, self esteem, multiple intelligences